(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article describes the policy of reintegration of the temporarily occupied territories of Ukraine and its legal foundations with the aim of developing proposals for its improvement. The political context is inherent in the reintegration of the temporarily occupied territories of Ukraine. Reintegration is one of the key tasks of Ukrainian state policy, which first of all requires careful preparation and determination of the mechanism for overcoming internal and external risks. It is noted that the policy of reintegration of the temporarily occupied territories of Ukraine has not been comprehensively regulated in a separate legal act. It is necessary to adopt the law on the reintegration of the de-occupied territories and to adopt the corresponding subordinate legal acts. The adoption of the Concept of reintegration of the de-occupied territories, as well as strategic documents on information and economic policy in the de-occupied territories, is a logical continuation of such a political decision. It has been proven that public participation in the policy of reintegration of the temporarily occupied territories of Ukraine contributes to the transparency, fairness and effectiveness of political decisions, as well as strengthening public trust. It was concluded that the formation of the reintegration policy of the temporarily occupied territories of Ukraine is an important task that requires a complex and systematic approach. The policy of reintegration should be based on the Constitution of Ukraine and be defined in a separate law of Ukraine, in addition, clear and consistent strategic bylaws are important. In the process of forming and implementing the reintegration policy of temporarily occupied territories, it is important to use the advantages of communication between the state and civil society. An effective reintegration policy should be based on a quality information policy, ensure the restoration of infrastructure and stimulate the economic development of the de-occupied territories.